2021
DOI: 10.3389/fphar.2021.680674
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Antiviral Activity of Glycyrrhizin and its Derivatives in Liquorice

Abstract: Liquorice is a traditional medicine. Triterpenoids such as glycyrrhizin and glycyrrhetinic acid are the main active constituents of liquorice. Studies have revealed that these compounds exert inhibitory effects on several viruses, including SARS-CoV-2. The main mechanisms of action of these compounds include inhibition of virus replication, direct inactivation of viruses, inhibition of inflammation mediated by HMGB1/TLR4, inhibition of β-chemokines, reduction in the binding of HMGB1 to DNA to weaken the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 113 publications
0
29
0
Order By: Relevance
“…GR has a high affinity for S protein-mediated cell binding and thus blocks binding of recombinant S protein to host cells (Li et al 2021 ). In addition, several reviews and in silico docking studies have provided evidence for the potent effects of GR against SARS-CoV-2 replication and virus S protein binding to host cells (Gomaa and Abdel-Wadood 2021 ; Diomede et al 2021 ; Ahmad et al 2021 ; Zheng et al 2021 ; Zhang et al 2021a ; Huan et al 2021 ). Although there are no experimental studies to date investigating the effect of BA against SARS-CoV-2, several studies have shown the antiviral effect of BA against many other viruses (Badria et al 2003 ; Von Rhein et al 2016 ; Goswami et al 2018 ; Si et al 2018 ; Xiao et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…GR has a high affinity for S protein-mediated cell binding and thus blocks binding of recombinant S protein to host cells (Li et al 2021 ). In addition, several reviews and in silico docking studies have provided evidence for the potent effects of GR against SARS-CoV-2 replication and virus S protein binding to host cells (Gomaa and Abdel-Wadood 2021 ; Diomede et al 2021 ; Ahmad et al 2021 ; Zheng et al 2021 ; Zhang et al 2021a ; Huan et al 2021 ). Although there are no experimental studies to date investigating the effect of BA against SARS-CoV-2, several studies have shown the antiviral effect of BA against many other viruses (Badria et al 2003 ; Von Rhein et al 2016 ; Goswami et al 2018 ; Si et al 2018 ; Xiao et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…G. glabra and its bioactive components is well recognized and reviewed through several authenticated research findings for accompanying antiviral effects against several kinds of viruses such as DNA virus like Herpes Simplex Virus-1, Kaposi sarcoma-associated herpesvirus, Varicella zoster virus, Epstein Barr virus, Human Cytomegalo virus, etc and RNA viruses such as Influenza A virus (IAV), H1N1 virus, H5N1 virus, Hepatitis C virus, Rotavirus, Newcastle disease virus, Human Immunodeficiency Virus, SARS-associated coronavirus and express its action via blocking the viral replication process ( Nasiriasl and Hosseinzadeh, 2007 ; Baltina et al, 2009 ; Anagha et al, 2014 ; Wang et al, 2015 ; Sun et al, 2019 ; Huaccho-Rojas et al, 2020 ; Huan et al, 2020 ; 2021 ). In an earlier study GD4 (without any glycyrrhizic acid), compound obtained from liquorice was found to be effective antiviral agent against RSV with median TC 50 (0.23 mg/ml), EC 50 (28.73 µg/ml) and TI (8) ( Wang et al, 2006 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%
“…In summary G. glabra induces macrophages and stimulate the immune response as an evidence from several study. Further, N-acetyl muramoyl peptide (glycyrrhizin derivative) has found to exhibit immune-stimulating efficiencies specially on influenza virus by suppression of viral replication ( Huan et al, 2021 ). Recently, a group of researcher showed that ethanol extract of G. glabra containing polysaccharides enhances the immunity through elevating the extents of serum IgG, IgM and IgA as well as by enhancing the prevalence of the lymphocytes in the spleen ( Ng et al, 2021 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The root of the traditional Chinese herb, Glycyrrhiza glabra, containing a triterpenoid compound called glycyrrhizin (20) (also known as glycyrrhizic acid or glycyrrhizinic acid), and its derivatives, exerts inhibitory effects on hepatitis C virus (HCV), HSV-1, influenza virus, and severe acute respiratory syndrome associated coronaviruses (SARS-COV) [161]. Several studies have reported that glycyrrhetinic acid, the product of body metabolism from 20, and other derivatives, demonstrated anti-HSV in vitro [85][86][87][88]162].…”
Section: Terpenoids With Potential Anti-herpetic Activitiesmentioning
confidence: 99%